Public management approaches to an aging workforce: organizational strategies for strategies for adaptability and efficiency - Wang, Zouhengrui; Fu, Jishan; Bai, Weijun (Frontiers in Psychology, 2024)
This study investigates the impact of psychological age climate on the motivation of aged workers in China and explores the mediating mechanisms at play. Two proposed chains of mediation capture the potential mechanisms underlying this process. The first chain involves the task and knowledge characteristics of work design, specifically autonomy arrangements and skill-based job demands, as mediators. The second chain focuses on the social and physical/contextual aspects of work design, including social support and ergonomic working conditions. The study sample consisted of 1,094 Chinese employees aged between 50 and 70 years (M = 55.66, SD = 4.274). Our findings reveal that a positive psychological age climate—organizational norms and practices that value and support older workers—significantly boosts their motivation to continue working. This enhancement in motivation is mediated by increased job autonomy and robust social support within the workplace, confirming that these elements are crucial for translating a positive age climate into tangible outcomes. Contrary to existing literature, our research does not support the mediating role of job design tailored to aged workers’ skills and ergonomic working conditions. This indicates that in the cultural and organizational context of China, where collective values and respect for elder wisdom predominate, autonomy and social support directly influence workers’ motivation more profoundly than ergonomic and job design considerations. The study underscores the importance of creating inclusive organizational cultures and implementing targeted support strategies to retain and engage aged workers effectively. It suggests that public policymakers and organizational leaders should focus on fostering positive psychological age climates and providing necessary autonomy and social resources to meet the unique needs of an aging workforce, thereby enhancing both individual and organizational outcomes in a globally aging society.